Assessment Of Oral Health Knowledge And Challenges In Oral Hygiene Practices Among Homeless Adults In Jalan Chow Kit, Kuala Lumpur - Nor Haliza Mat Baharin; Erma Fazira Muhammad; Nurul Najwa MdYusuf; Nor Azura Ahmad Tarmidzi (Taylor & Francis, 2024)
Indexed by WOS